L'adaptabilité : agir efficacement face au changement - Calarco, Allan (Guide "Transformer les idées en action.", 2012)
In today's business world, the complexity and pace of change can be daunting. Adaptability is a necessary skill for leaders to develop in order to respond effectively to this change. This book contributes to a greater understanding of adaptability and the cognitive, emotional, and dispositional flexibility it requires. Leaders will learn how to develop their own adaptability and to foster it in others, thereby becoming more effective for themselves, the people they lead, and their organizations.